Exploring the challenges of implementing COVID_19 guidelines: Experiences of commuters in the Copperbelt Province, Zambia. - Kalungwe, Mwamba; Karonga, Thamary; Mwale, Claude; Simwanza, Niza Rean; Mugala, Lameck; Mwewa, Jessie; Nyashanu, Mathew (Open Science Journal, 2024)
Background: The first case of COVID-19 in Zambia was confirmed on the 18th of March 2020, to date 320, 412 people have been infected and 3983 Covid related deaths have been reported. In Zambia, public transport is mainly by road, dominated by intra-city minibuses. This mode of transport particularly involve serious human interaction and compliance with Covid -19 preventive measures, especially in urban areas had not been systematically evaluated. Aims: To explore the challenges to compliance in implementing the recommended WHO COVID -19 guidelines in Copperbelt Province, Zambia. Design: An explorative qualitative study. Methods: Individual semi-structured interviews were conducted from February to April 2022 and, content analysis was used. Results: The following 5 major themes emerged: “perception and experiences about Covid 19; knowledge of prevention guidelines; attitudes towards implementation of the prevention guidelines; accessibility and availability of protective equipment; and, accessibility and availability of transport.” Drivers and conductors experienced tremendous reduction in income due to restricted movements of passengers as well as social distancing which called for a reduction in the number of passengers in a particular bus, cost of face masks and hand sanitizers. This left them with no profit and most of them were retrenched. Passengers reported discomfort caused by the face masks which prevented some of them from breathing properly, while others reported impact on their business and restriction in movements. A section of respondents felt that Covid was a hoax therefore prevention guidelines were an infringement on them. Conclusion: This study highlights the fact that creating an enabling environment for doing business is critical by ensuring Covid -19 prevention materials are subsidized or provided for free. In addition provision of loans to transporters to cushion the challenges are crucial. Furthermore there is need to maximize information dissemination to raise awareness and depoliticize the fight against Covid -19.